Lateral Gene Transfer (LGT) between Archaea and Escherichia coli is a contributor to the emergence of novel infectious disease - Faguy, David M (BioMed Central, 2003)
BACKGROUND: Lateral gene transfer is the major mechanism for acquisition of new virulence genes in pathogens. Recent whole genome analyses have suggested massive gene transfer between widely divergent organisms. PRESENTATION OF THE HYPOTHESIS: Archeal-like genes acting as virulence genes are present in several pathogens and genomes contain a number of archaeal-like genes of unknown function. Archaea, by virtue of their very different evolutionary history and different environment, provide a pool of potential virulence genes to bacterial pathogens. TESTING THE HYPOTHESIS: We can test this hypothesis by 1)identifying genes likely to have been transferred (directly or indirectly) to E. coli O157:H7 from archaea; 2)investigating the distribution of similar genes in pathogens and non-pathogens and 3)performing rigorous phylogenetic analyses on putative transfers. IMPLICATIONS OF THE HYPOTHESIS: Although this hypothesis focuses on archaea and E. coli, it will serve as a model having broad applicability to a number of pathogenic systems. Since no archaea are known vertebrate pathogens, archaeal-like transferred genes that are associated with virulence in bacteria represent a clear model for the emergence of virulence genes.